Can students with different language backgrounds profit equally from a language-responsive instructional approach for percentages? Differential effectiveness in a field trial. Issue 1 (2nd January 2023) - Prediger, Susanne; Neugebauer, Philipp
ABSTRACT: Language-responsive instructional approaches are intended to enhance the mathematics learning of students with low academic language proficiency, mostly by enriching mathematical content trajectories with systematic language-learning opportunities. However, little is known about their effects (and in particular differential effects) in linguistically diverse classrooms. The paper reports on a cluster-randomized field trial investigating the effectiveness of a language-responsive instructional approach for percentages in 38 mathematics classrooms with 655 seventh graders. The multilevel regression analysis shows that the intervention group developed significantly more conceptual understanding of percentages than the control group. In the intervention group, no differential effects were found for language proficiency, multilingual background, and immigrant status. These findings suggest that all students' access to mathematical conceptual understanding can be promoted.